Strategi Kepala Madrasah dalam Mengembangkan Kegiatan Ekstrakurikuler di MA Ma’arif Al Muhtadi Sendangagung Paciran Lamongan - Hidayatul Mufidah; M. Fathor Rohman; Arina Thoriqotul Firdaus (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
The development of extracurricular activities is important to do, because intracurricular activities are still lacking in developing the potential of students. So it is necessary to have companion activities that can help maximize the potential of students. This study aims to answer several problem formulations, namely, the strategy of the head of the madrasa in developing extracurricular activities, the supporting and inhibiting factors of the principal in developing extracurricular activities. In order to find out the problem and get accurate data, the researcher used observation, interview and documentation methods and used qualitative descriptive analysis techniques. The results of this study, that the principal's strategy in developing extracurricular activities at this madrasa are 1). by dividing into 2 parts in charge, namely PK IPNU IPPNU and Scouts; 2) by involving all stakeholders, especially waka students and coaches to participate in developing extracurricular activities; 3) guided by the vision and mission of the madrasa which reads